THE EFFECTIVENESS OF ABDOMINAL STRETCHING EXERCISES ON THE INTENSITY OF PRIMARY DYSMENORRHEA IN ADOLESCENT GIRLS IN EAST JAKARTA - Purwarini, Justina; Maura, Khanza; Yesaya, Fendy (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Background: The transition by childhood to adulthood is called adolescence, typically beginning at the age of 12–24 years. Female adolescence is marked by several changes, particularly in the development of the hormone’s estrogen and progesterone. One of the characteristics of women entering adolescence is menstruation. in the process of menstruation, women may endure unpleasant symptoms, such as dysmenorrhea or menstrual pain caused by excessive uterine contractions that can interfere by daily operations. Purpose: This study aimed to explore how effective abdominal stretching exercises are in decreasing the degree of menstrual pain endured by adolescent girls in East Jakarta. Methods: This study conducted a pre-experimental method utilizing a one-cohort pretest–posttest design approach. Outcomes: The outcomes implied that before doing the abdominal stretching exercises, most participants endured moderate menstrual pain (scale 2–6), by 33 respondents (55.0%) reporting this stage. After the exercise, the pain degree decreased to a mild stage (scale 1–4) in 50 respondents (83.3%). A total of 60 adolescents took a part in the study. Utilizing the Wilcoxon Signed Ranks Test, the analysis yielded a p-value of 0.000 that is lower than the significance stage of 0.05. This implies that abdominal stretching exercises were effective in decreasing dysmenorrhea degree among adolescent girls in East Jakarta. Conclusion: Abdominal stretching can boost blood flow, ease muscle tension in the abdominal area, and promote relaxation. These effects help lessen the degree of menstrual pain endured by individuals by dysmenorrhea.